STATE POLICY AS A TOOL FOR INCREASING THE INTERNATIONAL COMPETITIVENESS OF THE NATIONAL ECONOMY - Galaziuk , N.M. (The actual problems of regional economy development, 2025)
The article defines the role of the state's macroeconomic policy as a key tool for forming and increasing the international competitiveness of the national economy of Ukraine in the context of globalization challenges. It is proven that today a special place in ensuring the international competitiveness of Ukraine is played by state policy in the field of innovation. The author substantiates that in the context of globalization transformations, digitalization and economic instability, it is the state that must ensure the effective functioning of the competitive business environment. It is determined that the competitiveness of the national economy depends on the development of entrepreneurship, investment activity, technological innovations and effective institutional support. The purpose of the study is to substantiate the theoretical foundations and develop practical recommendations for increasing the role of the state in ensuring the competitive advantages of the national economy in the international business environment. The methodological basis of the work is a set of general scientific and special research methods, in particular analysis and synthesis, induction and deduction, comparative analysis, and a systemic approach. As a result of the study, the main institutional and instrumental mechanisms of state policy that can contribute to increasing the international competitiveness of the Ukrainian economy have been identified. The role of innovation, intellectual capital and technical modernization as key factors in ensuring sustainable economic growth has been revealed. The scientific novelty of the work lies in defining a two-level model of macroeconomic policy in the field of competitiveness and substantiating the need to integrate institutional support instruments with the priorities of industrial and technological development. The theoretical significance lies in deepening the understanding of competition policy as a system of measures to support national business. The practical significance of the study lies in outlining areas for improving state policy, taking into account the modern challenges of digitalization, globalization and economic instability, which can be used to increase the efficiency of regional management and economic planning.